Comparisions Of Electrothermal And Conventional Metal Bracket Debonding: An İn Vivo Study - Selim Arıcı; Tamer Türk; Mete Özer (Galenos Yayinevi, 1999)
This in vivo study was undertaken to examine and compare the frequencies of bond failure sites and bracket deformations, and patient discomfort levels during the electrothermal (ETD) and conventional (KD) debonding of metal brackets. Thirty female patients, ages 13 to 15, were included in this study. Half of the subjects right and the others left site anterior teeth were debonded with one of the debonding method. ETD was done with a modified soldering device. For KD, a pair of conventional debonding pliers was used. Both groups predominantly underwent bracket/resin interface failures. Chi-square analysis, however, showed a significant difference between both methods for the frequencies of ARI scores and bracket deformations, and for the patient discomfort levels. It is concluded that although ETD left more adhesive resin on the tooth surface, it caused a lower degree of patient discomfort and bracket deformation than KD during debonding of metal brackets.